Economic Impact of Zakat | الآثار الاقتصادية للزكاة - Wildanul Hakim (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2016)
This article discusses the Islamic rules and its influence on social economic life. Thisarticle would like to see as deep as if the teachings of attention to the economic aspects ofhuman life. This article tries to analyze the rules of zakat on Islam in the Quran andHadith pared with the economic approach. This article would like to conclude that therules of Islam does not deny the life of the world.